The results of treatment of osteoporosis in young women - Golański, Grzegorz; Urbaniak, Ireneusz (Menopause Review/Przegląd Menopauzalny, 2003)
Osteoporosis is a metabolic disease that has significant social meaning. The main problem are osteoporotic fractures which the most common are fractures of femoral neck, vertebral corpora, the distal epiphysis of radius, proximal epiphysis of humerus and the ribs. The material consists of female patients at the age between 45–55 who were treated at the clinic for the outpatients. Another criterion of qualifying to the program was the presence of at least two bone densytometries made within a period of 12 months. Patients were divided into two groups. The first group – patients treated with calcitonine and the second – patients treated with bisphosphonates. Patients of both groups have also been prescribed calcium and vitamin D3. The goal of the work was verification (with the bone densitometry) of the results of treatment in women at the age of 45–55 with the diagnosed osteoporosis and verification of number of osteoporotic fractures that happened during the treatment. Another goal was a comparison of the results of treatment in both of the groups. During the period of antyosteoporotic treatment 12 fractures were confirmed at 11 of patients. At another 3 patients treated also for additional diseases – factors of osteoporosis – 5 fractures were confirmed. The most important purpose of treatment of osteoporosis is a reduction of number of fractures. The clinical practice shows that bone mineral density is one of the numerous factors that have an influence on number of fractures. The results of this work confirm that thesis as a fact. In many cases in spite of treatment with drugs that significantly increase the mineral density of bones there was no improvement in results of densitometric examination. The increase of mineral bone density does not fully secure patient from fractures.